2019
DOI: 10.1021/acs.jmedchem.9b01369
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed, Conformationally Constrained Inverse Agonists of RORγt—Identification of a Potent, Selective Series with Biologic-Like in Vivo Efficacy

Abstract: RORγt is an important nuclear receptor that regulates the production of several pro-inflammatory cytokines such as IL-17 and IL-22. As a result, RORγt has been identified as a potential target for the treatment of various immunological disorders such as psoriasis, psoriatic arthritis, and inflammatory bowel diseases. Structure and computer-assisted drug design led to the identification of a novel series of tricyclic RORγt inverse agonists with significantly improved in vitro activity in the reporter (Gal4) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 73 publications
1
45
0
Order By: Relevance
“…Compared to structure 2 (Figure ), the side chain amide nitrogen in the new series (compounds 3 – 7 ) is sterically hindered because it is attached to the tricyclic core, which could potentially alter or slow down metabolic processes such as N-dealkylation. Because the reverse amide series was a logical extension from our earlier tricyclic pyrrolidine series where the nitrogen atom was a part of the ring system, as illustrated in 1 , , a number of side chains studied earlier were re-examined here. Molecular modeling studies revealed that the trajectory of the side chains in both tricyclic pyrrolidine and reverse amide series point toward the RORγt polar pocket, consisting of a network of residues including Glu286, Leu287, Arg364, and Arg367.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to structure 2 (Figure ), the side chain amide nitrogen in the new series (compounds 3 – 7 ) is sterically hindered because it is attached to the tricyclic core, which could potentially alter or slow down metabolic processes such as N-dealkylation. Because the reverse amide series was a logical extension from our earlier tricyclic pyrrolidine series where the nitrogen atom was a part of the ring system, as illustrated in 1 , , a number of side chains studied earlier were re-examined here. Molecular modeling studies revealed that the trajectory of the side chains in both tricyclic pyrrolidine and reverse amide series point toward the RORγt polar pocket, consisting of a network of residues including Glu286, Leu287, Arg364, and Arg367.…”
Section: Results and Discussionmentioning
confidence: 99%
“…85–23, revised 2011). Detailed biological experimental procedures, animal studies, and assay conditions used in this study can be found in our recent publications, refs . and .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, inverse agonists of RORγt have the potential for the treatment of a range of immune and inflammatory disorders. In continuation of our research in the same direction, , we recently reported a novel tricyclic RORγt inverse agonist, BMT-362265 , which was synthesized via coupling of the tricyclic core 10 with (1 R , 2 S , 4 R )-2-methylcyclohexane-1,4-dicarboxylic acid (Scheme ). This paper details an inexpensive, safer, and scalable synthetic route to the tricyclic core 10 of BMT-362265 .…”
Section: Introductionmentioning
confidence: 80%
“…We think that a statistical analysis of extensive structural information where one collectively examines protein-ligand contact interaction patterns may provide insight into this challenge. For this work, we studied 136 RORγ structures: 132 with one ligand (or ligand fragments) bound (100+ distinct ligands) from X-ray crystallography experiments ( Jin et al, 2010 ; Fujita-Sato et al, 2011 ; Fauber et al, 2013 ; Fauber et al, 2014 ; van Niel et al, 2014 ; Yang et al, 2014 ; Chao et al, 2015 ; Muegge et al, 2015 ; René et al, 2015 ; Santori et al, 2015 ; Scheepstra et al, 2015 ; Wang et al, 2015b ; Wang et al, 2015c ; Enyedy et al, 2016 ; Hirata et al, 2016 ; Hintermann et al, 2016 ; Marcotte et al, 2016 ; Olsson et al, 2016 ; Ouvry et al, 2016 ; Xue et al, 2016 ; Kallen et al, 2017 ; Kummer et al, 2017 ; Li et al, 2017 ; Noguchi et al, 2017 ; Carcache et al, 2018 ; Fukase et al, 2018 ; Gege et al, 2018 ; Gong et al, 2018 ; Kono et al, 2018 ; Narjes et al, 2018 ; Noguchi et al, 2018 ; Sasaki et al, 2018 ; Schnute et al, 2018 ; Shirai et al, 2018 ; Wang et al, 2018 ; Amaudrut et al, 2019 ; Duan et al, 2019 ; Hoegenauer et al, 2019 ; Kotoku et al, 2019 ; Lu et al, 2019 ; Marcoux et al, 2019 ; Sato et al, 2019 ; Strutzenberg et al, 2019 ; Tanis et al, 2019 ; von Berg et al, 2019 ; Yukawa et al, 2019 ; Zhang et al, 2019 ; Cherney et al, 2020 ; Duan et al, 2020 ; Gege et al, 2020 ; Harikrishnan et al, 2020 ; Jiang et al, 2020 ; Liu et al, 2020 ; Meijer et al, 2020 ;…”
Section: Introductionmentioning
confidence: 99%